2017
DOI: 10.1080/14767058.2017.1402878
|View full text |Cite
|
Sign up to set email alerts
|

The association of first trimester uterine arteries Doppler velocimetry with different clinical phenotypes of hypertensive disorders of pregnancy: a longitudinal study

Abstract: UtA Doppler velocimetry in the first trimester was strongly associated with HDP-IUGR all along gestation, as a proxy of placental insufficiency, and showed no association with HDP-AGAf. Our findings suggest an efficacy of first trimester UtA Doppler velocimetry to identify HDP-IUGR independently of the gestational age, and a limited value for HDP not associated with intrauterine growth restriction (IUGR).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…Specifically, low maternal cardiac output and high maternal peripheral vascular resistance are associated with raised impedance in the maternal uterine and fetal umbilical arteries. 36 Interestingly, there was no relationship with fetal cerebral Doppler impedance that indicated that the mechanism is unlikely to be mediated by hypoxia.…”
Section: Commentmentioning
confidence: 97%
“…Specifically, low maternal cardiac output and high maternal peripheral vascular resistance are associated with raised impedance in the maternal uterine and fetal umbilical arteries. 36 Interestingly, there was no relationship with fetal cerebral Doppler impedance that indicated that the mechanism is unlikely to be mediated by hypoxia.…”
Section: Commentmentioning
confidence: 97%
“…In normal pregnancy, uterine artery pulsatility index (UtA-PI) decreases with advancing gestation 1,2 . In hypertensive disorders of pregnancy (HDP), UtA-PI is higher than in normal pregnancy from as early as the first trimester; this difference persists throughout pregnancy, although the PI still decreases with advancing gestation 1,[3][4][5] . This difference is most apparent in early-onset HDP associated with fetal growth restriction (FGR) 1,[3][4][5] .…”
Section: Introductionmentioning
confidence: 99%
“…In hypertensive disorders of pregnancy (HDP), UtA-PI is higher than in normal pregnancy from as early as the first trimester; this difference persists throughout pregnancy, although the PI still decreases with advancing gestation 1,[3][4][5] . This difference is most apparent in early-onset HDP associated with fetal growth restriction (FGR) 1,[3][4][5] . High early-pregnancy UtA-PI has been attributed to impaired trophoblast invasion and poor spiral artery remodeling in pregnancies prone to HDP [6][7][8][9] .…”
Section: Introductionmentioning
confidence: 99%
“…This dualistic view of the pathogenesis of PE is important for both clinical and research reasons, but, not surprisingly, some risk factors or pathogenetic aspects can overlap. 14,15 Major challenges in modern obstetrics is the prediction of women at high risk of PE early in the first trimester. 14,15 Since the trophoblastic invasion and the consequent inflammatory reaction are among the earliest events in pregnancy, one could speculate that inflammation mediators might constitute adequate predictors.…”
Section: Introductionmentioning
confidence: 99%
“…14,15 Major challenges in modern obstetrics is the prediction of women at high risk of PE early in the first trimester. 14,15 Since the trophoblastic invasion and the consequent inflammatory reaction are among the earliest events in pregnancy, one could speculate that inflammation mediators might constitute adequate predictors. However, on the one hand, the selective dosage of a single cytokine lacks in specificity, and, on the other hand, the precise quantification of reactive oxygen species (ROS) is difficult.…”
Section: Introductionmentioning
confidence: 99%